Development and validation of three spectrophotometric methods for determination of pyridostigmine bromide in the presence of its alkaline-induced degradation product - Abdelaleem, Eglal Abdelhamid; Naguib, Ibrahim Ahmed; Abdallah, Fatma Fared; Ali, Nouruddin Wageih (European Journal of Chemistry, 2015)
Three simple, accurate and validated spectrophotometric methods were developed for the determination of pyridostigmine bromide (PB) in presence of its alkaline-induced degradation product, 3-hydoxy-N-methylpyridinium bromide (3-OH NMP) in powder form and in pharmaceutical formulations. Method A, is first derivative method (1D), which is based on measuring the peak amplitude of the first derivative spectra (1D) of PB at 260 nm. Method B, is first derivative of ratio spectra (1DD) which allows the determination of PB at 267.4 nm using (50 µg/mL) of 3-OH NMP as a suitable devisor. Finally, method C depends on mean centering of ratio spectra (MCR) of PB with different concentrations, which were recorded over 200-400 nm and divided by the spectrum of 20 µg/mL of 3-OH NMP as a devisor. The obtained ratio spectra were mean centered and the concentrations of PB were then determined from the calibration graphs obtained by measuring the amplitudes at 338 nm. The proposed methods were successfully applied for assay of PB both in pure form and in pharmaceutical formulations. The proposed methods were validated in compliance with International Conference on Harmonization (ICH) guidelines. The results obtained by the developed methods were statistically compared to those obtained by the reported HPLC method using F- and student's t-tests showing no significant difference regarding both accuracy and precision.